Pelatihan Dasar-Dasar ISO 9001:2015 Untuk Manajemen Administrasi Perkantoran - Widayat, Puspita Dewi; Wedhasari, Tyas (CV. IRA PUBLISHING, 2024)
The Quality Management System or ISO 9001:2015 is one of the tools to improve product quality. Office administration management is one of the variables that supports the optimal operation of an organization. Basic training in the implementation of ISO 9001:2015 is one effort to introduce new insights into management systems, particularly office administration management. The training provided to students of SMK 10 November in South Jakarta has made a significant contribution. This is one of the goals that can be achieved by Mercu Buana University as a collaborative partner to support better learning processes at SMK 10 November in South Jakarta. This new knowledge is expected to provide students with additional skills to compete in the industrial world. Community service activities support the enrichment of understanding and new insights into the implementation of ISO 9001:2015 as a tool in office administration management. The training was conducted through the delivery of materials and Q&A sessions related to the content, supplemented with case studies. The outputs of the training include the enrichment of materials for the participants, who are students of SMK 10 November in South Jakarta, a training implementation video, mass media publications, and scientific publications.